Kewajiban Pelaksanaan Penyimpanan Protokol Notaris Sebagai Arsip Negara Dalam Aspek Kepastian Hukum - Christiana Basoeki, Karin (Riviera Publishing, 2025)
The obligation of Notaries holding Protocols to submit Protocols received which at the time of submission are 25 years old or more to the Regional Supervisory Board in practice does not run as it should where the Protocols are still kept by the recipient of the Protocol until the Protocol is submitted to the next Protocol Holder, so that the responsibility of the Notary Protocol holder becomes longer than it should have been regulated by the applicable laws and regulations. As the recipient of the Protocol which is 25 years old or more, the obstacle faced by the Regional Supervisory Board is the unavailability of adequate storage space by the state as a form of implementation of the statutory regulations stating that Notary Protocols are state archives as per Law Number 2 of 2014 concerning amendments to Law Number 30 of 2004 concerning the Position of Notary (UUJN). Notary Protocols are state archives that must be guarded, secured, and protected by notaries as public officials until the time limit is determined by the law. Therefore, this study was conducted to explain the aspects of legal certainty that must be fulfilled by the state through the Regional Supervisory Board to carry out the storage of Notary Protocols that are 25 years old or more as state archives. So that the intent and purpose of storing the protocol can run well, and the duties and responsibilities of the notary can be protected.